The Role of Pancreatic Infiltrating Innate Immune Cells in Acute Pancreatitis - Cheng Peng; Zhiqiang Li; Xiao Yu (2020)
Acute pancreatitis (AP) is a leading cause of gastrointestinal-related hospital admissions with significant morbidity and mortality. Although the underlying pathophysiology of AP is rather complex, which greatly limits the treatment options, more and more studies have revealed that infiltrating immune cells play a critical role in the pathogenesis of AP and determine disease severity. Thus, immunomodulatory therapy targeting immune cells and related inflammatory mediators is expected to be a novel treatment modality for AP which may improve the prognosis of patients. Cells of the innate immune system, including macrophages, neutrophils, dendritic cells, and mast cells, represent the majority of infiltrating cells during AP. In this review, an overview of different populations of innate immune cells and their role during AP will be discussed, with a special focus on neutrophils and macrophages.